Religiosity, spirituality and psychotropic drug use (Archives of Clinical Psychiatry, 2007)
BACKGROUND: Religiosity and spirituality have been clearly identified as strong protective factors against drug use in many levels. OBJECTIVE: The present revision of literature intended to describe the main scientific studies that deal with the role of religiosity in the treatment and prevention of drug use. METHOD: The sources cited in this revision article are indexed in the databases PubMed and Scielo, between 1976 and 2006, treating questions relative to religiosity, spirituality and drug use. RESULTS: Studies have to the evidence that people who regularly attend a religious worship, of any kind, or that give relevant importance to their religious belief, or, still, that they practice daily the proposal of the professed religion, show minor licit and illicit durg use rate. In addition, drug addicts present better recovery rates when their treatment is permeated by a spiritual approach of any origin, when compared to drug addicts who are treated exclusively by conventional medicine. CONCLUSIONS: Due to the strong social assistance role of religions in Brazil, the exploration of this subject in the Brazilian context would be of great relevance for the public health.